Biodegradation of Soil Contaminated with Polycyclic Aromatic Hydrocarbons PAHs through Nitrogen Biostimulation - Fernández, Ernesto Delgado; Malo, Inés; Salinas, Jazmín; Sarmiento, Rosalía; García, Fernando Morales; Geraud-Aguilar, E. (Journal of Ecohumanism, 2024)
This study evaluated the effect of nitrogen on the biostimulation of microbial load in soil mesocosms contaminated with bunker oil. Urea was used as a nitrogen source, with C/N ratios of 60:1 and 100:10 established to analyze its impact on the biodegradation of polycyclic aromatic hydrocarbons (PAHs). Experiments were conducted in plastic trays containing 2 kg of soil contaminated with 8% bunker oil. Samples were taken on days 15, 30, 60, and 90, and chemical analysis was performed using gas chromatography-mass spectrometry (GC-MS). Results indicated that the treatment with a C/N ratio of 100:10 achieved the highest PAH reduction percentage (99.27%), demonstrating the efficacy of urea biostimulation. This study highlights the importance of optimizing nutrient proportions to enhance biodegradation efficiency in hydrocarbon-contaminated soils. The addition of urea is confirmed as a viable and economical solution for soil remediation, aligning with previous studies emphasizing the crucial role of nitrogen in microbial activity and the degradation of recalcitrant contaminants. In conclusion, incorporating urea as a nitrogen source proved to be an effective strategy for biostimulation and PAH biodegradation in soil mesocosms, offering a sustainable solution to mitigate hydrocarbon contamination.